Orthodontic approach in dental trauma: systematic review and meta-analysis - Martins, Christine Men; Batista, Victor Eduardo de Souza; Verri, Ana Caroline Gonçales; Verri, Fellippo Ramos; Gomes Filho, João Eduardo; Panzarini, Sonia Regina (ARCHIVES OF HEALTH INVESTIGATION, 2016)
Introduction: There is a high prevalence of dental trauma in patients in need of orthodontic treatment, so it is important the knowledge about the orthodontic approach in cases of traumatized teeth. Thus, this study conducted a systematic review about orthodontic approach in dental trauma. Materials and Methods: Two investigators performed a systematic review with meta-analysis. MEDLINE/PubMed and Cochrane Library supplied relevant data from studies published between February 2004 and September 2015 on the relationship between dental trauma and orthodontic treatment. Results: Susceptibility to pulp necrosis was the dichotomous outcomes measure evaluated by risk ratio (RR) and the corresponding 95% confidence intervals (CI). The quality was evaluated using the Oxford Centre for Evidence-Based Medicine (EbM) guidelines. A search strategy and application of eligibility criteria enabled selection and evaluation of four studies on orthodontic treatment in traumatized teeth. In total, 1.696 patients (average age 11.6 years) with orthodontic treatment over 24.2 months were studied, and 484 had already suffered dental trauma and undergone orthodontic treatment. The primary observed sequelae after orthodontic treatment indicated greater susceptibility to pulp necrosis in traumatized teeth compared to no previous trauma. The patients with orthodontically treated traumatized maxillary incisors were more susceptible to pulp necrosis (RR: 7.6; 95% CI: 3.64 to 15.87; p= 0.00001) compared to patients with previous dental trauma to the maxillary incisors and no subsequent orthodontic treatment. Conclusion: There is no well-established protocol for these cases; such treatment must be careful and respect the healing period post-trauma, when these teeth are more susceptible to pulp necrosis and pulp obliteration. Descriptors: Tooth Injuries; Wounds and Injuries; Tooth Avulsion; Orthodontics, Corrective.